Validity and reliability assessment of 3-D camera-based capture barbell velocity tracking device - Tomasevicz, C. L.; Hasenkamp, R. M.; Ridenour, D. T.; Bach, C. W. (Journal of Science and Medicine in Sport, 2020)
Velocity-based training (VBT) requires the monitoring of lift velocity plus the prescribed resistance weight. A validated and reliable device is needed to capture the velocity and power of several exercises. Objectives: The study objectives were to examine the validity and reliability of the Elite Form Training System® (EFTS) for measures of peak velocity (PV), average velocity (AV), peak power (PP), and average power (AP). Design: Validity of the EFTS was assessed by comparing measurements simultaneously obtained via the Qualisys Track Manager software (C-motion, version 3.90.21, Gothenburg, Sweden) utilizing 6 motion capture cameras (Oqus 400, 240 Hz, Gothenburg, Sweden). Methods: Six participants performed 6 resistance exercises in 2 sessions: power clean, dead lift, bench press, back squat, front squat, and jump squat. Results: Simple Pearson correlations indicated the validity of the device (0.982, 0.971, 0.973, and 0.982 for PV, AV, PP, and AP respectively) and ranged from 0.868 to 0.998 for the 6 exercises. The test-retest reliability of the EFTS was shown by lack of significant change in the Pearson correlation (<0.3% for each variable) between the 2 sessions. The multiple count error rate was 2.0% and the missed count error rate was 2.1%. Conclusions: The validity and reliability of the EFTS were classified as excellent across all variables and exercises with only one exercise showing a slight influence by the velocity of the movement.